2012
DOI: 10.4066/amj.2012.1267
|View full text |Cite
|
Sign up to set email alerts
|

Admission cardiotocography:Its role in predicting foetal outcome in high risk

Abstract: The admission CTG appears to be a simple non-invasive test that can serve as a screening tool in 'triaging' foetuses of high-risk obstetric patients in non-industrialised countries with a heavy workload and limited resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 5 publications
7
27
2
Order By: Relevance
“…The most common indication in non -reactive group was for fetal distress (75%). The present study has similar findings with Rahman et al 14 where in reactive AT group of 123 cases, 65 (52.8%) had normal vaginal delivery, 44 (35.8%) had LSCS and 14(11.4%) had instrumental delivery. In equivocal AT group of 23 cases, 12(52.2%) had normal vaginal delivery, 10 (43.5%) had LSCS and 1 (4.3%) had instrumental delivery.…”
Section: Figure 1: Admission Test Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The most common indication in non -reactive group was for fetal distress (75%). The present study has similar findings with Rahman et al 14 where in reactive AT group of 123 cases, 65 (52.8%) had normal vaginal delivery, 44 (35.8%) had LSCS and 14(11.4%) had instrumental delivery. In equivocal AT group of 23 cases, 12(52.2%) had normal vaginal delivery, 10 (43.5%) had LSCS and 1 (4.3%) had instrumental delivery.…”
Section: Figure 1: Admission Test Resultssupporting
confidence: 80%
“…This high percentage in ominous AT group shows the significant relationship between the abnormal CTG pattern and fetal distress as evident by babies with Apgar score <7 at five minutes after birth. In a study by Rahman et al 14 8.9% of the cases from reactive AT group of 77% had moderate to thick MSL where 6.5% had babies with Apgar score <7. Likewise in 14.4% of equivocal AT group, 39.1% had moderate to thick MSL where 26.1% had babies born with Apgar score <7.…”
Section: Figure 1: Admission Test Resultsmentioning
confidence: 99%
“…LSCS (16.2%) and IUGR (16.2%). This was compared to a study conducted by Rahman et al 10 where the majority of women (73.8%) were in the 21-30 years age group. 61.9% were primigravida while 38.1% females were multigravida.…”
Section: Discussionmentioning
confidence: 88%
“…The association was statistically significant (p< 0.05). The study by Rahman et al 10 have 72% patients with an ominous test had moderate-thick meconium stained liquor, compared to 39% and 9% in the equivocal and reactive CTG group respectively. (p<0.001)…”
mentioning
confidence: 97%
“…Although the evidence from previous randomised trials, and a systematic review, for IA use on labour admission, is compelling, conflicting findings from recent non‐randomised studies continue to provide some clinicians with a rationale for ACTG use. Rahman et al for example, in a study evaluating the role of ACTG, reported a low risk of fetal compromise during labour for women with a reactive ACTG compared with women with equivocal and ominous ACTGs; 6.9%, 39.9% and 84.6%, respectively ( P < 0.001) . The incidence of thick meconium‐stained liquor, admission to NICU and neonatal mortality were also significantly higher in the ominous and equivocal groups compared with the reactive ACTG group and operative birth for suspected fetal compromise was required in 5.5% ( n = 8/145) of women in the reactive group compared with 27.8% ( n = 5/18) in the equivocal group and 84.6% ( n = 11/13) of women in the ominous group.…”
Section: Discussionmentioning
confidence: 99%